Triterpenoid saponins and other glycosides from the stems and bark of Jaffrea xerocarpa and their biological activity. (September 2017) - Muhammad, Dima; Lalun, Nathalie; Bobichon, Hélène; Le Magrex Debar, Elisabeth; Gangloff, Sophie C.; Nour, Mohammed; Voutquenne-Nazabadioko, Laurence
Abstract: Six previously undescribed triterpenoid saponins and two previously undescribed nor lupane triterpenes were isolated with five known saponins, three known lupane derivatives, 17, 20-didehydro-20-deoxyjujubogenin, rutin, (±) 3α- O - β -d -glucopyranosyl-lyoniresinol, (±) 4- O - β -d -glucopyranosyl-maesopsin, three phenol glycosides, and uridine from the stems and bark of Jaffrea xerocarpa (Baill.) H. C. Hopkins & Pillon (= Basionym Alphitonia xerocarpus Baill.) (Rhamnaceae), an endemic tree of New Caledonia. The chemical structures of the purified compounds were identified by nuclear magnetic resonance and mass spectrometry. The isolated compounds were tested for their antioxidant, antityrosinase, antibacterial and cytotoxic activities. The aqueous methanol extract showed antioxidant activity (DPPH assay) due to the presence of rutin and other phenolic compounds. Three lupane triterpenes showed good cytotoxic activities against KB cells line (IC50 from 7.7 to 8.5 μM). The previously undescribed 2 α -formyl-A(1)norlup-20(29)-en-28-oic acid showed antibacterial activity against Staphylococcus aureus and Enterococcus faecalis with both MIC values of 4 μg/mL. Graphical abstract: Highlights: Five dammarane triterpenoid glycosides were isolated from Jaffrea xerocarpa. Three nor lupane triterpenoids were isolated from Jaffrea xerocarpa. The hydromethanolic extract showed good antioxidant activity (DPPH assay). A nor lupane triterpenoid showed antibacterial activity. Three lupane triterpenoids showed good cytotoxic activity against KB cells.